2022
DOI: 10.1007/s42994-022-00076-3
|View full text |Cite
|
Sign up to set email alerts
|

The application of CRISPR/Cas technologies to Brassica crops: current progress and future perspectives

Abstract: Brassica species are a global source of nutrients and edible vegetable oil for humans. However, all commercially important Brassica crops underwent a whole-genome triplication event, hindering the development of functional genomics and breeding programs. Fortunately, clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated (Cas) technologies, by allowing multiplex and precise genome engineering, have become valuable genome-editing tools and opened up new avenues for biotechnology. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 121 publications
0
11
0
Order By: Relevance
“…Therefore, CRISPR/Cas systems provide dynamic and effective immunity against invading genetic elements. Sequence-specific RNA–DNA recognition and cleavage by Cas nucleases make CRISPR/Cas systems useful as programmable genome editing tools [ 28 ].…”
Section: Crispr/cas: a Useful Genome Editing Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, CRISPR/Cas systems provide dynamic and effective immunity against invading genetic elements. Sequence-specific RNA–DNA recognition and cleavage by Cas nucleases make CRISPR/Cas systems useful as programmable genome editing tools [ 28 ].…”
Section: Crispr/cas: a Useful Genome Editing Toolmentioning
confidence: 99%
“…Then, Cas9 utilizes two distinct nuclease domains, HNH and RuvC-like, to cleave both strands of the target DNA, generating sequence-specific DSBs. This triggers two DNA repair systems, nonhomologous end-joining (NHEJ) and homology-directed repair (HDR) [ 28 ]. NHEJ, which is prevalent in most cells, is an error-prone pathway.…”
Section: Crispr/cas: a Useful Genome Editing Toolmentioning
confidence: 99%
“…The recent sequencing and assembly of the cotton genome has opened the door to the systematic study of gene function [2][3][4]. The emergence of modern biotechnologies, including single-cell RNA sequencing (scRNAseq) and genome editing, will promote the development of breeding strategies and basic research in cotton [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Most were conducted in Brassica oleracea or B. napus to improve commercially important agronomic traits or nutritional values such as seed oil, carotenoids, or glucosinolate contents . Most of these studies used CRISPR/CRISPR-associated protein 9 (Cas9) to generate insertions/deletions (InDels) in single or multiple genes [ 11 ]. Only a few studies have reported modifying genes using CRISPR/Cas9 in B. rapa .…”
Section: Introductionmentioning
confidence: 99%